Challenges and opportunities for re-framing resource use policy with practice theories: The change points approach. (May 2020) - Watson, Matt; Browne, Alison; Evans, David; Foden, Mike; Hoolohan, Claire; Sharp, Liz
Highlights: New change points approach enables policy engagement with socio-technical complexity. Effective engagement with complexity opens new opportunities for change initiatives. There is no clear binary between academic research and policy professionals. Translation of social theory insights to policy processes through co-production. Abstract: Concerns about the climate crisis and the escalating pace of global consumption are accelerating the pressure on governments to moderate public demand for resources like water, food and energy. Notwithstanding their increasing sophistication, standard behavioural change approaches continue to be criticised for a narrow understanding of what shapes behaviour. One alternative theoretical position comes from practice theories, which draw on interpretive and relational understandings to focus on practices rather than people's behaviour, and hence highlight the complex and distributed set of factors shaping resource use. While practice theories have gained considerable interest from policy institutions within and beyond the UK they so far have had limited impact upon policy. It has even been argued that there are insurmountable challenges in reconciling the ontological commitments of practice theories with the realities of policy processes. This article advances academic and policy debates about the practical implications of practice theories. It works with evidence from transdisciplinary research intended to establish whether and how key distinctive insights from social practice research can usefully be brought to bear on policy. We pursued this through co-productive research with four key UK national policy partners, focusing on effective communication of social practice research evidence on agreed issues. A key outcome of collaboratively negotiating challenging social theory to usefully influence policy processes is the 'Change Points' approach, which our partners identified as offering new thinking on initiatives promoting reductions in people's use and disposal of resources. The Change Points approach was developed to enable policy processes to confront the complexities of everyday action, transforming both how problems are framed and how practical initiatives for effecting change are developed. We discuss the case of food waste reduction in order to demonstrate the potential of Change Points to reframe behaviour change policy. We end the paper by addressing the potential and limitations of informing policy with insights from practice theories based upon the successes as well as the challenges we have met. This discussion has broader implications beyond practice theories to other fields of social theory, and to debates on the relations between academic research and policy more broadly. We argue that, through a co-productive approach with policy professionals, and so engagement with the practices of policy making, it is possible to provide a partial and pragmatic but nevertheless effective translation of key distinctive insights from practice theories and related research, to reframe policy problems and hence to identify spaces for effecting change for sustainability.